2011
DOI: 10.1149/1.3633297
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of a Channel Strain via Dry Oxidation of Recessed Source/Drain Si1−xGex Structures

Abstract: We investigated the effects of oxidation on recessed source/drain Si1-xGex structures. Epitaxial Si1-xGex films were deposited on recessed source/drain structures using a selective epitaxial growth process combined with ultrahigh-vacuum chemical vapor deposition and oxidized in dry oxygen ambient. Based on nano beam diffraction analyses, the channel strain was effectively enhanced at specific oxidation conditions. The increase in channel strain results from the formation of Ge-rich layers on the top surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In attempts to improve the hole mobility of p-channel MOSFET, numerous studies related to the growth of an epitaxial Si 1-x Ge x have been reported. [1][2][3][4] The selective epitaxial growth (SEG) process is essential for strained engineering as Si 1-x Ge x should be grown on source/drain (S/D) region of the device so the strain is generated at the channel region. 4 In this study, Si 1-x Ge x layers were grown in steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In attempts to improve the hole mobility of p-channel MOSFET, numerous studies related to the growth of an epitaxial Si 1-x Ge x have been reported. [1][2][3][4] The selective epitaxial growth (SEG) process is essential for strained engineering as Si 1-x Ge x should be grown on source/drain (S/D) region of the device so the strain is generated at the channel region. 4 In this study, Si 1-x Ge x layers were grown in steps.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The selective epitaxial growth (SEG) process is essential for strained engineering as Si 1-x Ge x should be grown on source/drain (S/D) region of the device so the strain is generated at the channel region. 4 In this study, Si 1-x Ge x layers were grown in steps. For each step of Si 1-x Ge x layers, crystallinities and strains were analyzed on S/D, S/D bottom and channel regions, on the purpose of figuring out how epitaxial Si 1-x Ge x film is grown and as the epitaxial layer is grown, how strain is generated.…”
Section: Introductionmentioning
confidence: 99%